PERSPEKTIF HOS TJOKROAMINOTO TENTANG PENDIDIKAN ISLAM - Endan Hamdan Ridwan (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2019)
This study attempts to describe HOS Tjokroaminoto's thinking about Islamic Education, this research is a library research study using a qualitative narrative approach. While the method used is descriptive qualitative with character studies. Study of character studies is a systematic study of the thoughts or ideas of a Muslim thinker. The results of his research are 1) Islamic character education really must be applied both in formal schools or family environments, to fortify themselves from the decadence of the modern Jahiliyah era. The character of Islamic education must go through: 2) Islamic education must be based on the Al-Qur'an and Hadith.